Resistance Testing of Salmonella sp. Isolated from Broiler Chicken against Antibiotics - Syafitri, Martiana; Erina, Erina; AK, M Daud; Ferasyi, Teuku Reza; Hamzah, Abdullah; Nazaruddin, Nazaruddin; Ismail, Ismail (Jurnal Medika Veterinaria, 2023)
Antibiotic resistance has become a global problem, this happens because strains of bacteria in the body are resistant to antibiotics, one of which is caused by improper use. This study aims to determine the resistance of Salmonella sp. isolated from broiler chickens to antibiotics. The method used for this study is the Kirby Bauer disc diffusion method. The research samples were eight isolates from broiler chickens collected by the Laboratory of Microbiology, Faculty of Veterinary Medicine, Universitas Syiah Kuala. This study used antibiotics amoxicillin, streptomycin, chloramphenicol, ciprofloxacin, gentamicin, and tetracycline. The data obtained are processed descriptively. The results showed five isolates (62.5%) showed multidrug resistance and very high levels of resistance to antibiotics from eight samples tested, namely tetracycline 87.5% (7/8), chloramphenicol 75% (6/8), amoxicillin 62.5% (5/8), and streptomycin 62.5% (5/8). Antibiotics that are still sensitive are gentamicin 62.5% (5/8) and ciprofloxacin 50% (4/8). Therefore, it can be concluded that Salmonella sp. has been resistant to several types of antibiotics.